Occupational Safety and Health in Peru - Ismael Cruz; Raul Huerta-Mercado (Ubiquity Press, 2015)
Peru is a country located on the Pacific coast of South America with a population of more than 30 million inhabitants. In the past 10 years, Peru has had a steady economic growth. Peru is predominantly an extractive industry country, but the manufacturing and construction sectors are booming. It is in this context that regulations have been implemented to protect the safety and health of workers. One of the most important regulations is the Law on Safety and Health at Work, which has been recently promulgated. Regulations are complemented by training and education in occupational safety and health. The measures are yet to be fully implemented thus a positive effect in reducing accidents and occupational diseases at work has not yet been seen.